Primary Health Care (PHC) Registered Nurses (RNs) as facilitators of healthcare access for recent immigrants in Ontario: An interpretive descriptive study - Ling, Eugenia (My University, 2024)
Background and Objectives: Recent immigrants experience unique challenges when accessing health services. Registered Nurses (RNs) working in primary health care (PHC) have the competencies and are well-positioned to facilitate healthcare access for immigrants. Aim: This study explored how PHC-RNs in Ontario support healthcare access and address barriers among recent immigrants. Methods: This study used a qualitative, interpretive descriptive approach and was informed by Levesque et al.’s (2013) access to care framework. Semi-structured interviews were conducted with 10 PHC RNs practising in Toronto, Ottawa-Gatineau, Hamilton, Kitchener-Cambridge-Waterloo, and London. Data were collected and analyzed concurrently using an inductive and deductive approach. Results: Findings show that PHC-RNs play instrumental roles in supporting recent immigrants through facilitating healthcare access across 9 dimensions of Levesque et al.’s (2013) access framework: (1) appropriateness, (2) availability and accommodation, (3) ability to perceive, (4) ability to engage, (5) ability to seek, (6) ability to reach, (7) affordability, (8) ability to pay, and (9) acceptability. RNs addressed significant challenges to health service access for recent immigrants, including language, geographical, and financial barriers. Several opportunities were identified to enhance the PHC RN clinical practice role to improve the delivery of PHC for recent immigrants, such as increasing organizational resources, utilizing their expertise and role beyond the PHC clinic, and promoting culturally appropriate care. Conclusions: PHC-RNs are key facilitators of healthcare access for recent immigrants by coordinating their care, educating, and connecting this population to services across the health system. However, there are opportunities to optimize nursing roles and more effectively utilize their scope of practice within interdisciplinary teams to promote the health of immigrants.
Keywords: Primary Health Care; Primary Care; Nursing; Registered Nurses; Immigrant Health; Access to Care; Role Optimization; Interpretive Description; Qualitative Research